Public awareness of the link between alcohol and cancer in England in 2015: a population-based survey - Penny Buykx; Jessica Li; Lucy Gavens; Lucie Hooper; Melanie Lovatt; Elena Gomes de Matos; Petra Meier; John Holmes (BMC, 2016)
Abstract Background Public knowledge of the association between alcohol and cancer is reported to be low. We aimed to provide up-to-date evidence for England regarding awareness of the link between alcohol and different cancers and to determine whether awareness differs by demographic characteristics, alcohol use, and geographic region. Methods A representative sample of 2100 adults completed an online survey in July 2015. Respondents were asked to identify which health outcomes, including specific cancers, may be caused by alcohol consumption. Logistic regressions explored whether demographic, alcohol use, and geographic characteristics predicted correctly identifying alcohol-related cancer risk. Results Unprompted, 12.9% of respondents identified cancer as a potential health outcome of alcohol consumption. This rose to 47% when prompted (compared to 95% for liver disease and 73% for heart disease). Knowledge of the link between alcohol and specific cancers varied between 18% (breast) and 80% (liver). Respondents identified the following cancers as alcohol-related where no such evidence exists: bladder (54%), brain (32%), ovarian (17%). Significant predictors of awareness of the link between alcohol and cancer were being female, more highly educated, and living in North-East England. Conclusion There is generally low awareness of the relationship between alcohol consumption and cancer, particularly breast cancer. Greater awareness of the relationship between alcohol and breast cancer in North-East England, where a mass media campaign highlighted this relationship, suggests that population awareness can be influenced by social marketing.